Toxinas da peçonha de Bothrops moojeni Hoge, 1966 (Squamata: Viperidae) que interferem na agregação plaquetária - Queiroz, Mayara Ribeiro de (2015)
Cap. II: In this paper, we describe the purification/characterization of BmooAi, a new toxin from Bothrops moojeni that inhibits platelet aggregation. The purification of BmooAi was carried out through three chromatographic steps (ion-exchange on a DEAE-Sephacel column, molecular exclusion on a Sephadex G-75 column, and reverse-phase HPLC chromatography on a C2/C18 column). BmooAi was homogeneous by SDS-PAGE and shown to be a single-chain protein of 15,000 Da. BmooAi was analysed by MALDI-TOF Spectrometry and revealed two major components with molecular masses 7824.4 and 7409.2 as well as a trace of protein with a molecular mass of 15,237.4 Da. Sequencing of BmooAi by Edman degradation showed two amino acid sequences: IRDFDPLTNAPENTA and ETEEGAEEGTQ, which revealed no homology to any known toxin from snake venom. BmooAi showed a rather specific inhibitory effect on platelet aggregation induced by collagen, adenosine diphosphate, or epinephrine in human platelet-rich plasma in a dose-dependent manner, whereas it had little or no effect on platelet aggregation induced by ristocetin. The effect on platelet aggregation induced by BmooAi remained active even when heated to 100°C. BmooAi could be of medical interest as a new tool for the development of novel therapeutic agents for the prevention and treatment of thrombotic disorders. Cap. III. Snake venoms contain complex mixture of nonenzymatic and enzymatic compounds which interfere in platelet aggregation. Peptides that actives platelet aggregation were purified from Bothrops moojeni venom by two chromatographic steps (ion-exchange and molecular exclusion). Peptides-induced platelet aggregation was inhibited by monoclonal anti-integrin α2b (CD41) and anti-GP1BA antibodies. These results indicate that these peptides may activate platelets by interaction with GPIb or vWF and culminates in activation of αIIbβ3 integrin.